2008
DOI: 10.1111/j.1095-8339.2008.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

On the identity of turmeric: the typification of Curcuma longa L. (Zingiberaceae)

Abstract: Although Curcuma L. (Zingiberaceae) is a conserved name, with C. longa L. as its conserved type, the type of C. longa is still uncertain. Numerous discussions about the identity of the taxon called C. longa by Linnaeus have been followed by various attempts to rename turmeric, suggestions as how to settle the type and proposals to conserve the name from a later author in order to stabilize the situation. Unfortunately, none of the previous proposals can be upheld for reasons which are discussed in this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Two analysed populations of C. longa did not cluster together. They may have originated from different cultivars or cryptic taxa (Leong‐Škorničková et al ., 2007, 2008b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two analysed populations of C. longa did not cluster together. They may have originated from different cultivars or cryptic taxa (Leong‐Škorničková et al ., 2007, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…sexual, vegetative or both) and ploidy (6 x , 9 x , 15 x ; ploidy levels represented by just one population were excluded), a non‐parametric Kruskall–Wallis test was performed in PAST (Hammer, Harper & Ryan, 2001), as sampling did not meet the criterion of classical ANOVA of independence among observations (uneven number of population per species). The ‘population’ of C. longa L. (Kerala) was removed from the analysis because we suspected that this sample was an artificial mixture of different cultivars or even species (see Leong‐Škorničková et al ., 2008b).…”
Section: Methodsmentioning
confidence: 99%
“…The typification of historical taxa in Zingiberaceae has never been a straightforward issue (Škorničková and Sabu 2005, Leong‐Škorničková et al 2008, 2010). While in a previous work Jenjittikul and Larsen (2000) indicated that the Wallich specimen, Wall.…”
Section: Discussionmentioning
confidence: 99%
“…This sheet is selected here as the lectotype. For the complex taxonomic history of C. longa and designation of lecto-, epi-and neotypes of the names involved see Leong-Škorničková & al. (2008b).…”
Section: Curcuma Karnatakensismentioning
confidence: 99%